1994
DOI: 10.1056/nejm199404213301603
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Need for Amniocentesis in Women 35 Years of Age or Older with Serum Markers for Screening

Abstract: Prenatal screening of serum to generate individual estimates of the risk of Down's syndrome in the fetus can provide a basis for decision making in the cases of women 35 years of age or older, as it does in younger pregnant women, and is an alternative to current testing practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(88 citation statements)
references
References 19 publications
6
79
0
3
Order By: Relevance
“…Second-trimester maternal serum samples from Down syndrome and unaffected pregnancies were collected as part of a previous Maternal and Child Health-sponsored trial (MCJ-237014) between 1990 and 1992 (12 ). Briefly, 14 prenatal diagnostic centers in California and elsewhere in the United States recruited women already scheduled to have an amniocentesis between 14 and 21 weeks of gestation, usually because of advanced maternal age.…”
Section: Methodsmentioning
confidence: 99%
“…Second-trimester maternal serum samples from Down syndrome and unaffected pregnancies were collected as part of a previous Maternal and Child Health-sponsored trial (MCJ-237014) between 1990 and 1992 (12 ). Briefly, 14 prenatal diagnostic centers in California and elsewhere in the United States recruited women already scheduled to have an amniocentesis between 14 and 21 weeks of gestation, usually because of advanced maternal age.…”
Section: Methodsmentioning
confidence: 99%
“…Among immunoassays, RIA, enzyme immunoassay (EIA), and ELISA have been developed and applied in screening for Down syndrome since the 1980s (6,21,22 ). Serum screening has shown to be cost-effective for detecting Down syndrome (23 ) and can reduce the need for invasive amniocentesis (24,25 ). However, recent studies revealed poor accuracy and imprecision of RIA in measuring uE 3 compared with results obtained from liquid chromatographytandem mass spectrometry (LC-MS/MS) analyses, and poor agreement of uE 3 concentrations was observed between RIA and chemiluminescent immunoassay methods (26,27 ).…”
mentioning
confidence: 99%
“…This is probably due to abnormal division of the egg, called no disjunction. The traditional age at which a woman is considered to be at high risk for chromosomal abnormalities is 40 and also miscarrying which is the loss of pregnancy before 20 weeks gestation [14].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The clinical implication of MS-AFP are elevated in cases of neural tube defects, underestimation of gestational age, threatened spontaneous abortion, and as increased placental transfer also occur in multiple pregnancies and low MS-AFP is associated with log standing fetal death, down syndrome, tiresome 13, tiresome 18, and pseudo pregnancy [14]. Interfering factors, obesity cause low MS-AFP, race (higher in black from 10% to15% low in Asian and also insulin dependent diabetes mellitus results in low MS-AFP.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%